Pengaruh Indeks Saham Global Terhadap Indeks Harga Saham Gabungan (IHSG) pada Bursa Efek Indonesia - Sakul, Ernest (JBE (Journal of Business and Economics); Volume 10 No.2, 2011 JBE UNKLAB, 2011)
This paper seeks to find out wheter foreign stock indices (Dow Jones, NYSE, FTSE, DAX, NIKKEI, HANG SENG, STI, KOSPI, ASX200 and KLSE) significantly influence the IHSG prior and after the global financial crisis. The sample consist of 10 foreign stock indices over the period 2006 to 2008 and 2009 to 2011. The study uses simple regression analysis with foreign stock indices as independent variable and IHSG as dependant variable. In order to find the most influence stok foreign indices to IHSG the correlation method is employed. Result of test indicates that for year 2006 to 2008 Dow Jones, NYSE, FTSE,DAX, and STI influence the IHSG. For year 2009 to 2011 the foreign indices that have influenced IHSG are Dow Jones, NYSE, FTSE, DAX, and NIKKEI. In addition, the most influencing influencing stock index is FTSE.